Pharmacokinetic/pharmacodynamic analysis of tedizolid phosphate against Staphylococcus aureus and Streptococcus pneumoniae in children, adolescents, and adults by Monte Carlo simulation - Xiao-Chen Wei; Ming-Feng Zhao; Hai-Rong Lv; Xia Xiao (Journal of Global Antimicrobial Resistance)
Objective: The objective of this study was to investigate the cumulative fraction of response of various dosage regimens of tedizolid phosphate against Staphylococcus aureus and Streptococcus pneumoniae in children, adolescents, and adults. Methods: Monte Carlo simulations were performed using previously published pharmacokinetic parameters and pharmacodynamic data to evaluate the efficacy of the simulated dosage strategies in terms of area under the concentration-time curve/minimum inhibitory concentration targets of tedizolid. Results: According to the results of the Monte Carlo simulations, currently approved dosage regimens of tedizolid phosphate were effective in the treatment of acute bacterial skin and skin structure infections (ABSSSIs) caused by methicillin-susceptible S. aureus and methicillin-resistant S. aureus (MRSA) including vancomycin-intermediate, heterogeneous vancomycin-intermediate, and daptomycin-non-susceptible MRSA in adult and paediatric patients aged 12 y and older. High-dose regimens of tedizolid phosphate should be the preferred option to optimize efficacy against ABSSSIs caused by linezolid-resistant MRSA, particularly chloramphenicol-florfenicol resistance-mediated isolates. The dosage regimens of 3 and 4 mg/kg/d of tedizolid phosphate were appropriate to treat ABSSSIs caused by methicillin-susceptible S. aureus and MRSA in children aged 2–6 and 6–12 y, respectively. Approved dosage regimens of tedizolid phosphate for patients older than 12 y may be sufficient against S. pneumoniae pneumonia but insufficient for S. aureus pneumonia. For neutropenic patients, almost all the simulated regimens of tedizolid phosphate were ineffective against S. aureus and S. pneumoniae. Conclusions: These pharmacokinetics/pharmacodynamics-based simulations rationalize and optimize the dosage regimens of tedizolid phosphate against S. aureus and S. pneumoniae in children, adolescents, and adults.